Perlindungan Hukum Terhadap Wisatawan Dalam Rangka Pemanfaatan Produk Dan Jasa Pariwisata Syariah (Halal Tourism) - Elan Jaelani (JES (Jurnal Ekonomi Syariah), 2018)
Tourism is one of the five priority development sectors in 2017 set by President Joko Widodo, in addition to the food, energy, maritime sectors, as well as industrial zones and Special Economic zones (KEK). Based on data from the Central Statistics Agency (BPS), the contribution of the tourism sector to Indonesia's foreign exchange is experiencing growth from year to year. This article aims to examine the field of sharia tourism (halal tourism) in terms of understanding and perspective in the field of sharia law and economics, and specifically directed to the discussion of legal protection for tourists in the context of the utilization of sharia tourism products and services (halal tourism). Sharia tourism sector (halal tourism) is a new field and is a part of Indonesia's efforts in developing and developing sharia economic and business systems as an alternative to the country's economic development. Through this research, it is found that the implementation of sharia tourism activities (halal tourism) in Indonesia still does not have adequate legal instruments and specifically regulates sharia tourism activities, including the legal rules related to legal protection of tourists. Through this research, it is found several legal instruments that can be used as alternatives in the framework of efforts to provide legal protection for the use of Islamic tourism products and services. The legal instruments include UU No. 8 of 1999 concerning Consumer Protection and UU No. 33 of 2004 concerning Halal Product Guarantee, in both legal instruments there are at least several provisions that can be used as guidelines and legal umbrella, among them are; related to the fulfillment of the right of tourists to get halal food and beverage products; the right of tourists to get services in accordance with sharia principles; the right of tourists to avoid misconduct, khurafat, pornography, liquor, and drugs; and fulfillment of tourist rights to access to worship. Keywords: Sharia Tourism, Consumer Protection Law, Halal Security Law, DSN-MUI Fatwa